2015
DOI: 10.1111/1365-2664.12524
|View full text |Cite
|
Sign up to set email alerts
|

Ecological traits affect the sensitivity of bees to land‐use pressures in European agricultural landscapes

Abstract: Summary Bees are a functionally important and economically valuable group, but are threatened by land‐use conversion and intensification. Such pressures are not expected to affect all species identically; rather, they are likely to be mediated by the species' ecological traits.Understanding which types of species are most vulnerable under which land uses is an important step towards effective conservation planning.We collated occurrence and abundance data for 257 bee species at 1584 European sites from surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
133
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(150 citation statements)
references
References 60 publications
7
133
1
9
Order By: Relevance
“…Within characterised bees there was a strong relationship between diet breadth and frequency of occurrence, with more generalist species found on a greater number of farms. Whilst earlier studies have shown that generalist bees are less sensitive to agricultural intensification (Bommarco et al 2010;De Palma et al 2015), the level of generalisation has not previously been shown to be a good predictor of frequency of occurrence. As more specialised bees are de facto less flexible in their dietary choices, the loss of floristic diversity resulting from agricultural intensification is likely to be the main driver behind their range declines over the past century (Scheper et al 2014;Ollerton et al 2014).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Within characterised bees there was a strong relationship between diet breadth and frequency of occurrence, with more generalist species found on a greater number of farms. Whilst earlier studies have shown that generalist bees are less sensitive to agricultural intensification (Bommarco et al 2010;De Palma et al 2015), the level of generalisation has not previously been shown to be a good predictor of frequency of occurrence. As more specialised bees are de facto less flexible in their dietary choices, the loss of floristic diversity resulting from agricultural intensification is likely to be the main driver behind their range declines over the past century (Scheper et al 2014;Ollerton et al 2014).…”
Section: Discussionmentioning
confidence: 91%
“…However, there are still important knowledge gaps relating to the conservation of wild bees, in part relating to an incomplete understanding of their agro-ecology (Dicks et al 2013). Previous authors have found that bee diet breadth is associated with sensitivity to habitat loss and agricultural intensification, with generalists faring better than specialists (Bommarco et al 2010;De Palma et al 2015). However, much of this analysis has been conducted at the categorical level of generalist or specialist, and it is not clear to what extent the level of generalisation within generalist species is also associated with species persistence.…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistent or insignificant relationships between bee richness and selected land-use variables are probably due to the relatively coarse scale of the analysis used in our study (Rollin et al 2015). To fully understand the effects of land-use change on bee diversity, further data are required on how ecological traits mediate species responses to human pressures (De Palma et al 2015).…”
Section: Discussionmentioning
confidence: 97%
“…As addressed, dramatic LULC change in Greater Shanghai and Greater Hangzhou, particularly recent expansion of developed land at the cost of semi-natural and natural lands, has resulted in a fragmented landscape and unbalanced patterns of ecological services delivery at a regional level, considering the relationship between spatial allocation of ecosystem services and human needs. Some specific ecosystem functions affected by LULC change and landscape fragmentation, such as pollination disturbance, habitat loss, landscape connectivity loss, which can be elaborated with one or several assumptions and empirical interpretations, such as pressures from land-use change and intensification [51,52], species' functional traits influenced sensitivity to human-dominated land use [53], the isolating effects of different patterns [54], and human-induced shifts in the functional structure of biological communities with possible repercussion on important ecosystem functions and services [55]. However, when focusing on interpreting the mechanism underlying the cause-effect relationship between anthropogenic large-scale LULC change, landscape fragmentation, and influenced ecosystems' functioning, the aforementioned assumptions and empirical interpretations may be problematic.…”
Section: Revisiting the Cause-effect Relationship Between Lulc Changementioning
confidence: 99%